2021
DOI: 10.22492/ije.9.5.03
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Socioemotional Skills and Decision-Making Styles in Health Students

Abstract: Higher education in health study programs is particularly focused on the development of technical skills, despite there being a consensus on the importance of training students regarding socioemotional and life skills. The aim of this study was to characterize and explore correlations between socioemotional skills and decision-making styles in undergraduate health students. Undergraduate students (18–25 years old) were recruited at a School of Health Sciences in Portugal. Participants were characterized in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although decision-making is a new examination and explanation for the prediction of basic psychological needs and life goals and the aspirations of emerging adults in South Africa, what can also be learnt from the findings is that awareness, as alluded to by Ryan and Deci (2018), becomes an important theoretical component in Self-Determination The- Using the seminal work within Self-Determination Theory, the results in the study suggest that the satisfaction of the basic psychological needs for autonomy, relatedness, and competence were significantly predicted for the emerging adults in the study when the 'why' or rather the decision-making process was vigilant or adaptive decision-making. Vigilant or adaptive decision-making styles have previously been predictors of positive affect (Filipe et al 2020), assertiveness (Silva et al 2021), satisfaction with life (Filipe et al 2020), and improved decisional self-esteem (Filipe et al 2020) in previous studies. In the current study, it can be seen that a positive interaction was found between adaptive or vigilant decision-making and the satisfaction of the basic psychological needs which promote the health and well-being of emerging adults.…”
Section: Discussionmentioning
confidence: 87%
“…Although decision-making is a new examination and explanation for the prediction of basic psychological needs and life goals and the aspirations of emerging adults in South Africa, what can also be learnt from the findings is that awareness, as alluded to by Ryan and Deci (2018), becomes an important theoretical component in Self-Determination The- Using the seminal work within Self-Determination Theory, the results in the study suggest that the satisfaction of the basic psychological needs for autonomy, relatedness, and competence were significantly predicted for the emerging adults in the study when the 'why' or rather the decision-making process was vigilant or adaptive decision-making. Vigilant or adaptive decision-making styles have previously been predictors of positive affect (Filipe et al 2020), assertiveness (Silva et al 2021), satisfaction with life (Filipe et al 2020), and improved decisional self-esteem (Filipe et al 2020) in previous studies. In the current study, it can be seen that a positive interaction was found between adaptive or vigilant decision-making and the satisfaction of the basic psychological needs which promote the health and well-being of emerging adults.…”
Section: Discussionmentioning
confidence: 87%
“…This should be done by seeking motivating educational strategies to promote independent judgment and critical awareness because physiotherapists need to make decisions to help patients in their recovery. 7 As Silva et al, 8 pointed out, training in skills and abilities in the socioemotional sphere is crucial to train health professionals in clinical decision‐making.…”
Section: Introductionmentioning
confidence: 99%